X-1(3x-9)=5

Simple and best practice solution for X-1(3x-9)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-1(3x-9)=5 equation:


Simplifying
X + -1(3x + -9) = 5

Reorder the terms:
X + -1(-9 + 3x) = 5
X + (-9 * -1 + 3x * -1) = 5
X + (9 + -3x) = 5

Reorder the terms:
9 + X + -3x = 5

Solving
9 + X + -3x = 5

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + X + -9 + -3x = 5 + -9

Reorder the terms:
9 + -9 + X + -3x = 5 + -9

Combine like terms: 9 + -9 = 0
0 + X + -3x = 5 + -9
X + -3x = 5 + -9

Combine like terms: 5 + -9 = -4
X + -3x = -4

Add '3x' to each side of the equation.
X + -3x + 3x = -4 + 3x

Combine like terms: -3x + 3x = 0
X + 0 = -4 + 3x
X = -4 + 3x

Simplifying
X = -4 + 3x

See similar equations:

| 2(m+5)=7 | | 4(-3)+3y=27 | | 2(.9x-1.5)=18.6 | | X+(7-x)=7 | | 2(x+6)-2=16-5x-6+7x | | 2(0.9x-1.5)=18.6 | | -5+7(x-4)=15x+2-8x | | (4x-1)2=1499 | | 7(a-7)+13=5(a-6) | | 8x-9=6x+13 | | 28x-7=49 | | 12x^2-176x+480=0 | | 1=1/3a-5 | | 4=2.6x | | 3(17)-(9n)=24 | | 2ln(x-2)-ln(x^2-4)+ln(3)=0 | | -2(y-3)+y=12 | | 5f+2=-4+2f-8 | | 2.75+.003+.158=2.938 | | 9m-2m=77 | | 4g+g=12 | | 3a-2a=12 | | 4xz=2104 | | 700/15 | | 3x+x=1 | | 1/cotu | | 5f+2=-42f-8 | | 2sectheta-2/1-costheta=2sectheta | | n+72=180 | | 6a+9=8 | | 55b^2-155b-30= | | 50/y=y/2 |

Equations solver categories